THE ROLE OF CORPORATE GOVERNANCE IN UZBEK BUSINESSES - Qudratilloh Nosirjonov (World Scientific Research Journal, 2025)
Abstract: CSR is Corporate Governance in which corporate objectives have to be directed towards the creation of value in pro-social and environmental manners. This paper concerns the relevance of CSR to Uzbek firms and discusses its ability to generate revenue, and comply to appropriate standards. Here, it is also necessary to declare the objectives of the paper, which is to outline the key points of CSR’s development and its significance and discuss its current and potential threats and opportunities for businesses in the context of Uzbekistan, with the emphasis made on the absence of research gaps in the existing literature. Using the principles of qualitative research, this article analyses the viewpoints of the main stakeholders, defines the obstacles that hound the advancement of a valid and successful framework of CSR in the companies of Uzbekistan, and provides practical recommendations to attain this goal.